2021
DOI: 10.3390/ijerph18041530
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Embedded in What We Do for Every Child”: A Qualitative Exploration of Early Childhood Educators’ Perspectives on Supporting Children’s Social and Emotional Learning

Abstract: Early childhood educators play an important role in supporting children’s social and emotional development. While a growing body of research has examined the impact of curriculum-based social and emotional learning (SEL) programs on child outcomes, the approaches educators use to strengthen children’s social and emotional functioning through their everyday practices are less defined. This study explored Australian early childhood educators’ perspectives on children’s social and emotional development, the appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…For instance, some participants recognized that attempts at providing training within their professional setting have not been successful because of staff turnover. Consistent with prior research, a lack of monetary support for both training around mental health and workforce stability are barriers (Blewitt et al, 2021;Isaksson et al, 2017). While the present research suggests that early childhood educators may benefit from further training and support around young children's mental health, systemic challenges persist in making these improvements difficult (Askell-Williams & Murray-Harvey, 2013;Reinke et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…For instance, some participants recognized that attempts at providing training within their professional setting have not been successful because of staff turnover. Consistent with prior research, a lack of monetary support for both training around mental health and workforce stability are barriers (Blewitt et al, 2021;Isaksson et al, 2017). While the present research suggests that early childhood educators may benefit from further training and support around young children's mental health, systemic challenges persist in making these improvements difficult (Askell-Williams & Murray-Harvey, 2013;Reinke et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…Although the etiology of early childhood mental health challenges is wide-ranging, research has consistently demonstrated that parents play an important role in shaping children's early emotional experiences (Blewitt et al, 2021). As identified by the early childhood educators in the present study, parents and families are essential when thinking about the proximal risks to young children's mental health.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As authors, we have seen, used and participated in every part of this model in practice. From unpacking educator tacit knowledge (for example, Blewitt et al , 2021), observing practice expertise and discretion in program delivery (for example, Morris et al , 2019), to the rare use of program theory in implementation (for example, O’Connor et al , 2020). In addition, all authors have been the researcher in residence among many community service organisations across Victoria, Australia.…”
Section: Contribution Of Realist Research Methodology In the Model’s Developmentmentioning
confidence: 99%